Pertumbuhan dan Produksi Tanaman Kacang Kedelai Terhadap Pemberian Pupuk Kotoran Sapi dan Poc Kulit Pisang - Ariani Syahfitri Harahap; Maimunah Siregar; Fahrur Rozi Perangin Angin (UNIVERSITAS LABUHANBATU, 2023)
The purpose of this study was to determine the growth and production of soybean plants (glycine max L) with the response to cow dung and banana peel POC fertilizers and their interactions. This research method used a factorial randomized block design (RAK) consisting of 2 factors with 16 treatment combinations and 2 replications so that 32 research plots were needed. The first factor studied was the treatment of cow dung fertilizer with the symbol